2013
DOI: 10.1002/cphc.201300066
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Role of Iodine Doping in Improving Photovoltaic Performance of Dye‐Sensitized Hierarchically Structured ZnO Solar Cells

Abstract: We report two novel types of hierarchically structured iodine-doped ZnO (I-ZnO)-based dye-sensitized solar cells (DSCs) using indoline D205 and the ruthenium complex N719 as sensitizers. It was found that iodine doping boosts the efficiencies of D205 I-ZnO and N719 I-ZnO DSCs with an enhancement of 20.3 and 17.9 %, respectively, compared to the undoped versions. Transient absorption spectra demonstrated that iodine doping impels an increase in the decay time of I-ZnO, favoring enhanced exciton life. Mott-Schot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 81 publications
0
9
1
Order By: Relevance
“…Dopants will ll the holes in the cell, thus increasing the recombination injected electron in the semiconductor. 34 Several materials such as iodine, 45 B, 46 Ag, 47 Li, 48 La, 49 Sr, 50 In, 51 and Nd 52 could be doped into the semiconductor lm of ZnO, according to some reports. Zhao et al used iodinedoped ZnO-based as a photoanode in dye-sensitized solar cells with indoline D205 and N719 as the sensitizers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dopants will ll the holes in the cell, thus increasing the recombination injected electron in the semiconductor. 34 Several materials such as iodine, 45 B, 46 Ag, 47 Li, 48 La, 49 Sr, 50 In, 51 and Nd 52 could be doped into the semiconductor lm of ZnO, according to some reports. Zhao et al used iodinedoped ZnO-based as a photoanode in dye-sensitized solar cells with indoline D205 and N719 as the sensitizers.…”
Section: Introductionmentioning
confidence: 99%
“…The efficiencies of the D205-I-ZnO based DSSC and N719-I-ZnO based DSSC were enhanced by 20.3% and 17.9%, respectively. 45 Mahmood and Park reported a cell fabricated with ZnO nanosheets doped with boron and using the N3 dye as a sensitizer, achieving a signicant enhancement in PCE (6.75%) in contrast to the undoped ZnO nanosheets (2.62%) and BZO lms only including nanosized crystallites (3%). 46 The work from Lanjewar et al revealed that upon doping with Ag, the band gap is sharply reduced and the resulting Ag:ZnO photoelectrode could absorb the visible light range to a great extent.…”
Section: Introductionmentioning
confidence: 99%
“…In continuation of previous studies (Zhao et al, 2013;Zheng et al, 2017), intrinsic ZnO and iodine-doped ZnO were grafted onto the glass beads through the SILAR method. Initially, glass beads were etched by dipping in 30% HNO 3 solution overnight at 30 °C, followed by washing with ethanol and deionized water.…”
Section: Grafting Of Intrinsic and Iodine-doped Znomentioning
confidence: 97%
“…ZnO CL pre-treatment and TiO 2 PL post-treatment. Herein it is worth noting that hierarchical IZnO aggregates instead of pure ZnO were chosen as the photoanode material mainly based on their proven multi-benefits: large surface area for dye adsorption, efficient scattering centers for enhanced light-harvesting efficiency, porous structure beneficial to good access of electrolyte to the dye, and additional light absorption in visible region as well [24,25]. More importantly, our previous work has demonstrated that the PCE of I-ZnO aggregates based DSC is obviously higher than that of ZnO aggregates based DSC.…”
Section: Introductionmentioning
confidence: 99%